2017
DOI: 10.1007/s00253-017-8315-4
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of denitrifying anaerobic methane-oxidizing microorganisms in a continuous-flow sponge bioreactor

Abstract: Anaerobic treatment of sewage has many advantages; however, the effluent contains high levels of dissolved methane. In this study, we investigated the use of a closed-type downflow hanging sponge (DHS) reactor for application of the denitrifying anaerobic methane oxidation (DAMO) reaction for nitrogen and dissolved methane removal. When using nitrate, the DAMO reaction achieved a denitrification rate of 84.4 g N m day, which is close to that required for practical application of denitrification to anaerobic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…3), with the caveat that these high rates may not exist in nature. Specically, nitrite-based DAMO in bioreactors usually shows methane oxidation at 0.00004-22.31 mmol CH 4 cm À3 d À1 , 22,49,53,62,63,98,110,[224][225][226][227][228][229] oen higher than nitrite-DAMO observed in terrestrial and marine environments. Besides, unlike sulfate-AOM, it seems that the nitrite-DAMO is not limited by methane.…”
Section: Some Of the Possibly Highest Aom Ratesmentioning
confidence: 88%
“…3), with the caveat that these high rates may not exist in nature. Specically, nitrite-based DAMO in bioreactors usually shows methane oxidation at 0.00004-22.31 mmol CH 4 cm À3 d À1 , 22,49,53,62,63,98,110,[224][225][226][227][228][229] oen higher than nitrite-DAMO observed in terrestrial and marine environments. Besides, unlike sulfate-AOM, it seems that the nitrite-DAMO is not limited by methane.…”
Section: Some Of the Possibly Highest Aom Ratesmentioning
confidence: 88%
“…Previous studies have confirmed that Group A had the ability to oxidize methane by enrichment culture and genomic analysis ( Ettwig et al, 2009 ; He et al, 2015 ; Wang et al, 2016 ; Xu et al, 2018 ). Recent studies have also enriched Group B, indicating that it may also have the ability to oxidize methane ( Hatamoto et al, 2017 ; Ma et al, 2017 ). These results implied that the DAMO process may play an important role in reducing methane emissions in the river ecosystem, while its in-situ activity needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that the ruminal nitrogen increased significantly following dietary nitrate supplementation (Guo et al ., 2009), and it indicated that other pathway is also involved in ruminal nitrate metabolism. The DAMO process, which has been widely detected in different environments where nitrate is available (Ettwig et al ., 2009; Shen et al ., 2014; Wang et al ., 2017) and was accelerated by the addition of nitrate (Hatamoto et al ., 2017), uses NO3/NO2 as the electron receptor to oxidize CH 4 . In this process, both NO3 and NO2 can be reduced to N 2 .…”
Section: Introductionmentioning
confidence: 99%